(untitled) (Training and Practice : Journal of Educational Sciences, 2018)
We have been teaching biology and chemistry in secondary grammar schools with outstandingly high academic reputation for almost twenty years. We have always payed attention to articles which are about the situation of natural science subjects. We have been reading a decreasing trend in the number of pupils who are interested in these natural science subjects and that their scientific knowledge has become less competitive, thus the succes rate has dropped. However, students in our school showing curiosity and the number of schoolchildren who are interested in natural science subjects have been growing steadily. What could be the reason for this contrast? We hope that the applied methods we use in everyday classes hasve a prominent role in this. For the significance of these methods we bring some good examples from our own experience and make suggestions for improvement.